Improvement of power quality of a 200 kW grid-connected PV system - Manoj Saini; Shagufta Khan; Amit Kumar Sharma; Sunil Kumar Chaudhary; Kiran Srivastava; Puneet Chandra Srivastava; Sumit Saini (Institute of Advanced Engineering and Science, 2023)
In order to enhance electricity quality, a grid-connected photovoltaic (PV) system simulation is presented in this study. A 200 kW photovoltaic system is integrated to a utility grid and loads. A 25 kV 3-level insulated gate bipolar transistor (IGBT) bridge converter is used. Through this system integration of a renewable energy source with a non-renewable source is achieved. This system also wins over the intermittent nature of the renewable source (solar energy) and non-reliability of conventional sources (utility grid). Power and signal quality for various signals such as ripple factor and total harmonic distortion has improved. The suggested system is investigated using MATLAB/Simulink environment. Total harmonic distortion (THD) in voltage and current, ripple factor correction is also incorporate in the MATLAB model.